Aerodynamic flow control for a generic truck cabin using synthetic jets. Issue 168 (September 2017) - Minelli, G.; Hartono, E. Adi; Chernoray, V.; Hjelm, L.; Krajnović, S.
Abstract: This experimental work presents the achievement in drag reduction with the use of active flow control (AFC) for a generic bluff body. Experiments were done in the Chalmers University closed loop wind-tunnel at Reynolds number R e = 5 × 10 5 . The R e is based on the undisturbed velocity U i n f = 20 m/s and the width of the model W = 0.4 m. The model consists of a simplified truck cabin, characterized by sharp edge separation on top and bottom edges and pressure induced separation on the rounded vertical side edges. The pressure induced separation reproduces the flow detachment occurring at the front A-pillar of a real truck. The investigation of the unactuated and actuated flow was conducted by means of time-resolved particle image velocimetry (PIV). Loudspeakers were used as the actuation device. These were characterized before the actuation study, highlighting an interesting analogy between actuation frequency and jet vortex pair size. The effects of different actuations were evaluated with hot wire anemometry. The effect of the actuation was studied using phase averaging and modal analysis. A notable reduction of the side recirculation bubble was observed. The nature of the separation mechanism was investigated and related to different actuation frequencies spanning the range 1 < F + < 6.2 . As for the R e, the non-dimensional frequency F + is based on the undisturbed velocity U i n f and the width of the model W .